If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 2x = 3x + 8 Reorder the terms: 7 + 2x = 8 + 3x Solving 7 + 2x = 8 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 7 + 2x + -3x = 8 + 3x + -3x Combine like terms: 2x + -3x = -1x 7 + -1x = 8 + 3x + -3x Combine like terms: 3x + -3x = 0 7 + -1x = 8 + 0 7 + -1x = 8 Add '-7' to each side of the equation. 7 + -7 + -1x = 8 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = 8 + -7 -1x = 8 + -7 Combine like terms: 8 + -7 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1
| -17=-204 | | 3x/9x^2-6x | | 5(2-y)/2=-y | | 0.2f+06(f+20)=-8+0.4f | | y^2-(5/3)y=-(25/36) | | 4a+a-4= | | 6+6r=8r | | X+25=28 | | 4c-6=9 | | 2^2/2^-3 | | 3X+5-2=15 | | 2x+6/8x-12 | | 5(3x-5)=15x-25 | | 2(5-x)=5(x+3) | | 63/3^2(5)(5-3) | | 42-2w=4 | | W/2=32 | | 0.50x+0.15(30)=45.5 | | 4y-26-6y+33= | | 5r-45/20=3r-18/3 | | x/10-7/5=x/5-1 | | b/6+3=-7 | | 4z+11=27 | | (2a+3b-4c)+(a-3b-4c)= | | xy=-49 | | 28=12+r*55/(r+55) | | 7.2=42+3-32 | | 21=12+r*55/(r+55) | | 1/6(x+3)=3x-2(3-x)-8 | | (x-2)*(x+1)=x*x-10 | | 1/3(x-2)=3x-2(x-1)+22/3 | | 12-7x=-6x |